Kepatuhan Indonesia Dalam Upaya Melindungi Hak Kekayaan Intelektual Dalam Trade And Investment Framework Agreement Dengan Amerika Serikat - Yuda Wiratama; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Piracy in intellectual property arises from the times that continue to take advantage of the development in technology. Various advantages have been arises from this phase of the development, such as an easy access to information, the availability of various information to the ease of convenience that occurs as a result of the technology development. Until then, the protection of intellectual property, which is the right of every community in the world becomes an issue that is the joint responsibility of the countries in the world. Indonesia and United States of America are taking an advantage in Intellectual Property Rights development. These two countries hid a bilateral cooperation in the economic field called Trade Investment Framework Agreement signed in 1996 which aims to protect the intellectual property rights of each country. Both country, United States of America and Indonesia through this agreement increase trust and enhance a good image for both countries in relation to compliance with international agreements. This study uses the concept of compliance approach in determining the attitude of two countries, and talks about efficiency, national interests and norms.